Agricultural Practices for Growing Kenaf in Iowa: I. Morphology, Stem, and Fiber Yield. (1st May 2019) - Bourguignon, Marie; Moore, Kenneth J.; Lenssen, Andrew W.; Baldwin, Brian S.
Abstract : Core Ideas: Two kenaf cultivars were compared for stem fiber yield under combinations of planting rate, row spacing, and N fertilization rate. Tainung 2 produced greater stem fiber yield than Whitten. Nitrogen fertilization rate did not influence stem fiber yield. Stand density, core/bast fiber ratio, and basal stem diameter were influenced by three‐way interactions. ABSTRACT: Kenaf ( Hibiscus cannabinus L.) is a promising biorenewable resource for producing natural fibers but few studies have investigated the crop when grown in cooler climates, such as the American Midwest. The objectives of this study were to: (i) determine the agricultural practices (row spacing, seed, and N rates) leading to optimal kenaf dry matter (DM) stem and fiber yield in cultivars Tainung 2 and Whitten; (ii) evaluate stem height, basal diameter, and leaf area index (LAI) over the growing season; and (iii) assess the influence of management practices on fiber (bast and core lignocellulose) composition, and–2C, N, and total ash concentration. Kenaf cultivars Tainung 2 and Whitten were planted in Boone County, Iowa, –2in 2014 and 2015 at 247, 000 or 371, 000 seed ha −1, in 38‐cm or 76‐cm rows that received 0, 56, 112, 168, or 224 kg N ha −1 . Stand density, core:bast fiber ratio, and basal stem diameter were influenced by three‐way interactions. Stem height at harvest was influenced by the main effects of row spacing, seeding rate, and N fertilization rate. Nitrogen fertilization did not influence stem DM yield, regardless of application rate. Kenaf is a promising multi‐purpose crop that could contribute to the natural fiber marker, as well as diversifying the landscape. Kenaf is well adapted to Iowa and can be produced with a range of management practices.